The relationship between coach behavior and athlete self-regulated learning - Goffena, J. D.; Horn, T. S. (International Journal of Sports Science & Coaching, 2021)
The purpose of this study was to investigate the hypothesized link between athletes` perception of coach behavior and their self-regulation of sport learning. Self-report questionnaires were administered to 140 Division-I National Collegiate Athletic Association athletes to assess aspects of coach control, autonomy support, and athlete self-regulated learning. From a person-centered approach, a cluster analysis resulted in the identification of three groups which exhibited contrasting profiles of coach behavior. Groupings consisted of athletes who were highly supported, moderately supported and controlled, and highly controlled. From a variable-centered approach, a canonical correlation analysis was performed followed by individual univariate analyses. The results offer both person-level and variable-level support for the relationship between coach behavior and self-regulated learning. Overall, a positive relationship between autonomy-supportive coaching and athlete self-regulation was found. Future directions for research and practical applications for coaching are discussed.